THE EFFECT OF INSIDE-OUTSIDE CIRCLE (IOC) TECHNIQUE ON STUDENTS’ SPEAKING ABILITY AT SMA NEGERI 1 KABANGKA - Saputri, Dia Ayu; Sale, Firdaus; Siam, Siam (Journal of Teaching of English, 2020)
The purpose of conducting this research was to examine the effect of Inside-Outside Circle technique on students’ speaking ability at SMA Negeri 1 Kabangka. The population of this research was all the second grade students of SMA Negeri 1 Kabangka which consisted of five classes while the sample of this research was the second grade science program two (XI IPA2) which consisted of 24 students. This research was conducted in pre-experimental research design. The data of this research were collected by giving pre-test and post-test to students. The data was analyzed by using SPSS 16.0 version (descriptive analysis and inferential statistics). Descriptive analysis was used to describe the maximum scores, minimum scores, mean score and standard deviation while the inferential statistic was used to examine the hypothesis. The result showed that there was an improvement of the students’ speaking ability. It can be seen from the mean score of post-test was 52.89, while the mean score of pre-test was 29.45. In order to prove the hypothesis, the researcher took the conclusion by comparing between the values of Sig (2 tailed) with the significance α value. It showed that the value of Sig (2 tailed) was 0.000 while the significance α value was 0.05. Therefore, it can be concluded that the value of Sig (2 tailed) was lower than the significance α value (0.000 < 0.05). In other words, the alternative hypothesis (H1) was accepted. It was meant that Inside-Outside Circle had a significant effect on students’ speaking ability at SMA Negeri 1 Kabangka.